The developmental uses of counterpart funds - Maxwell, Simon; Owens, Trudy; Institute of Development Studies (Brighton, England) (Brighton, England : Institute of Development Studies, 1991)
This paper examines various counterpart funding across the non-profit organisation or within the national and international community. The study is concerned with the developmental uses of counterpart funds in solving macro-economic problems associated under developing countries. The aim is to provide better ways in utilizing the accrued funds for developmental concerns.
"June 1991."
Includes bibliographical references (p. 43-48).
asm; 12/04/19
Loans
Keywords: Counterpart funds